Autoimmune processes in the personal computer users as possible causes of physical illnesses - Kulish, S. A.; Куліш, С. О. (г. Шымкент: Серпилис, 2016)
The problem of the harmful effects of the computer, such as the monitor, on the human body has acquired a truly global scale. In 1992, the share of so-called "ergonomic" diseases in the United States accounted for more than 50% of all occupational diseases, and the dynamics of their growth exactly matched the development of computerization in the country. Such ailments are accumulated gradually, but if time does not take action, can lead to total or partial disability. In the early 90s the US and European insurance companies have been hit hard by the epidemic, "ergonomic" disease that has led to the funding of research in this direction. Causes of "computer disease" has not yet been fully elucidated. It may be noted that throughout the history of human development it has not had to deal with such a load mode and thus influence how you operate the computer, so that his body and mind did not have time to adapt. At the same time today, the question for most people - to use a computer or not, is not worth it. Anyway, for many people, the computer has become an important and necessary part of life. The purpose of the researching. To determine the influence of the computer work on the development of the somatic diseases.
Keywords: тези